PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG DIRUGIKAN ATAS SITUS BELANJA ATAS TRANSKSI JUAL BELI SECARA BELANJA ONLINE - Meliyani Turnip; Selamat Lumban Gaol (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The main problems of this research are how the buying and selling process occurs on online shopping sites and how business actors are held accountable for losses suffered by consumers in online transactions. This study uses a quantitative method with a normative juridical approach. The data sources include laws and regulations, books, journals, encyclopedias, and other relevant written works. Data processing and analysis were conducted by collecting, reviewing, and analyzing literature and related documents, followed by editing, data reduction, and conclusion drawing. The results of the study indicate that the buying and selling process consists of four stages: offer, acceptance, payment, and delivery. If a consumer suffers a loss, the business actor is required to fully compensate the expenses incurred by the consumer, including both the shipping cost and the price of the purchased item. The implications of this research highlight the need for clear regulations in implementing online transactions, especially in cases of fraud or negligence by business actors who fail to deliver goods to consumers. If a seller is proven negligent three times and refuses to provide compensation or take responsibility, the government should take action by blocking the online store from conducting further internet-based transactions.